Evaluating the Pancasila Student Profile Strengthening Project Using the CSE UCLA Evaluation Model - Indra; Ambiyar; Muhammad Giatman; Waskito (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project (P5) at SMKN 1 Luak District, focusing on applying holistic, contextual, learner-centered, and explorative principles. The research method used is descriptive qualitative with a case study approach. Data were collected through interviews, observations, and documentation and analyzed using the CSE-UCLA evaluation model, which includes the stages of System Assessment, Program Planning, Program Implementation, Program Improvement, and Program Certification. The results showed that implementing P5 in SMKN 1 Luak District still faces various obstacles. The holistic principle has not been optimized due to the lack of integration between learners, teachers, and local communities. The contextual principle has not been fully implemented due to the lack of relevance of the project theme to local needs. In addition, the learner-centered principle is still weak due to the dominance of teachers in the learning process. In contrast, limited facilities and lack of training for teachers hamper the explorative principle. In conclusion, implementing P5 in this school still needs improvement in planning, teacher coordination, learner involvement, and program evaluation. The main recommendations from this study are to improve teacher training, learner involvement in planning, and the selection of themes that are more relevant to local conditions.